Zener Pinning of Grain Boundaries and Structural Stability of Immiscible Alloys - Koju, R. K.; Darling, K. A.; Kecskes, L. J.; Mishin, Y. (JOM (1989), 2016)
Immiscible Cu-Ta alloys produced by mechanical alloying are currently the subject of intensive research due to their mechanical strength combined with extraordinary structural stability at high temperatures. Previous experimental and simulation studies suggested that grain boundaries (GBs) in Cu-Ta alloys are stabilized by Ta nano-clusters coherent with the Cu matrix. To better understand the stabilization effect of Ta, we performed atomistic computer simulations of GB–cluster interactions in Cu-Ta alloys with various compositions and GB velocities. The study focuses on a single plane GB driven by an applied shear stress due to the shear-coupling effect. The results of the simulations are in close quantitative agreement with the Zener model of GB pinning. This agreement and the large magnitude of the unpinning stress confirm that the structural stability of these alloys is due to the drastically decreased GB mobility rather than a reduction in GB energy. For comparison, we simulated GB motion in a random solid solution. While the latter also reduces the GB mobility, the effect is not as strong as in the presence of Ta clusters. GB motion in the random solution itself induces precipitation of Ta clusters due to short-circuit diffusion of Ta in GBs, suggesting a possible mechanism of cluster formation inside the grains.